TO STUDY THE EFFECT OF BRAHM MUHRUAT JAGRAN ON MENTAL HEALTH WSR TO ANXIETY & DEPRESSION - Kulratan singh (International Journal of Ayurveda and Pharma Research, 2015)
World today has lot more psychological problem than physical suffering. In fact it can be said that not only diagnosed psychiatric patients but every human being who is running for survival is facing some kind of mental or psychological disturbances. Nearly 1/4th of all the patients who seek treatment are said to be present with psychological problems. About 15% patients require immediate psychiatric help. On the basis of the description available in various treatises of Ayurveda and Astrology, Sattvavajaya Chikitsa is helpful in the treatment of psychiatric disorders. So we prevent our self from disorders which occurs due to imbalances, and after removing imbalances and maintaining balance between mind and body, we are able to get complete health. Sattvavajaya Chikitsa is taken as the major line of treatment in the management of mental disorders. Therefore it was decided to launch a clinical trial on a group of which could be safe, effective, cheap and easy for the management of mental diseases, and help to maintain mental health. For this purpose following procedures may be suggested to control the growing of stress disorders: Brahma muhurat jagran. 30 clinically diagnosed patients of Anxiety and Depression were treated with Brahma muhurat jagran for 2months. It can be concluded that there is very close correlation of Ayurveda with Astrology and Spirituality along with pathogenesis of various diseases particularly Manas Roga (Mental Illness) and a combined approach delivers much better results.